DETERMINANTS OF ACADEMIC DISHONESTY AMONG STUDENTS AT COLLEGES IN YOGYAKARTA - Purwagesti O.E; Dekar Urumsah (International Journal of Economic Integration and Regional Competitiveness, 2024)
General Background: Academic fraud is a persistent challenge in higher education, undermining the integrity of academic institutions and compromising educational outcomes. Spesific Background: Yogyakarta, as a hub of higher education in Indonesia, faces increasing concerns regarding academic cheating among students, calling for a deeper understanding of its underlying causes and mitigating factors. Knowledge Gap: Despite the prevalence of studies on academic dishonesty, limited research explores the role of intrinsic factors such as student learning motivation in the context of academic fraud. Aims: This study aims to investigate the determinants of academic cheating by examining the influence of pressure, ability, opportunity, and rationalization. Additionally, it evaluates the role of learning motivation in moderating academic fraud. Results: The findings reveal that pressure does not significantly influence academic fraud, while ability, opportunity, and rationalization positively affect such behavior. Conversely, learning motivation demonstrates a negative effect on academic cheating, indicating its protective role. Novelty: By integrating the Fraud Diamond Theory with the learning motivation variable, this study offers a novel approach to understanding academic fraud in higher education. Implications: The findings provide theoretical insights into the interplay between fraud determinants and motivational factors. Practically, they enable educational institutions to design targeted interventions and prevention strategies to minimize academic dishonesty and foster a culture of integrity among students.